CLINICAL SIGNIFICANCE OF CORRELATIONAL RELATIONSHIPS BETWEEN LABORATORY PARAMETERS IN POST-KIDNEY TRANSPLANT PATIENTS (Global Conference on Multidisciplinary Research and Innovation, 2026)
Kidney transplantation has become the most effective treatment modality for end-stage chronic renal failure, demonstrating superior outcomes in patient survival and quality of life compared to hemodialysis and peritoneal dialysis. Globally, the number of kidney transplants continues to grow year on year — more than 25,000 procedures were performed in the United States alone in 2022, and in 2018 a total of 95,479 transplants were recorded worldwide across North America, Europe, the Asia-Pacific region, Southeast Asia, the Eastern Mediterranean, and Africa.